THE PEACOCK IN SUFI COSMOLOGY AND POPULAR RELIGION: Connections between Indonesia, South India, and the Middle East - Bruinessen, Martin van (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2020)
In various cultural and religious contexts, from West Asia to Southeast Asia, we come across a number of quite similar creation myths in which a peacock, seated on a cosmic tree, plays a central part. For the Yezidis, a sect of Sufi origins that has moved away from Islam, the Peacock Angel, who is the most glorious of the angels, is the master of the created world. This belief may be related to early Muslim cosmologies involving the Muhammadan Light (Nur Muhammad), which in some narratives had the shape of a peacock and participated in creation. In a different set of myths, the peacock and the Tree of Certainty (shajarat al-yaqīn) play a role in Adam and Eve’s fall and expulsion from Paradise. The central myth of the South Indian Hindu cult of the god Murugan also involves a tree and a peacock. The myth is enacted in the annual ritual of Thaipusam, like the Nur Muhammad myth is still enacted annually in the Maulid festival of Cikoang in South Sulawesi. Images of the peacock, originating from South India, have moved across cultural and religious boundaries and have been adopted as representing the different communities’ peacock myths.